Contextual diversity in telephone interpreting: Voices from healthcare interpreters in Scotland - Angelelli, Claudia V.; Ross, Jonathan Maurice (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This study conducted in Scotland focuses on the contextual factors that shape healthcare interpreters’ performance when they interpret over the telephone. It draws on the findings of two focus groups (n = 5 and 7) conducted in a Scottish urban area in 2017 among healthcare interpreters with experience in telephone interpreting (TI). The participants shared their experiences in TI as they related to issues that include (1) the impact of different equipment used by interpreters and clients respectively and (2) the interpreting strategies and techniques deployed in TI. Another issue that emerged from the focus groups was work–life balance. Judging by their contributions, healthcare interpreters are influenced by a multitude of factors when they interpret over the telephone, some of which have been accorded sufficient significance in the literature. Among the less-discussed factors are the specific kind of equipment used by healthcare providers and the policy of the interpreter’s employer regarding the use of mobile phones. The participants’ input suggests that they respond to the challenges of TI linked to the use of certain technologies with assertiveness and creativity, although they may not be fully aware of the consequences of some of their behaviours. This article highlights the value of focus groups in exploring diversity in a situated practice.